2021
DOI: 10.3390/foods10081940
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Makes a Healthy and Tasty Traditional Indonesian Goat Meatball, ‘Bakso’

Abstract: Meatballs are popular in Asia and traditionally made from beef or chicken with tapioca (≈8% wt/wt) as filler. Tapioca has a high glycaemic index (GI); therefore, rice bran was evaluated as a substitute to create a healthier meatball of acceptable quality. Substitution of tapioca with rice bran (100:0; 75:25, 50:50; 25:75; 0:100% tapioca: % rice bran) decreased the starch content (7.8 to 3.3%) and GI (56.08 to 43.85) whilst increasing the protein (10.9 to 12.8%) and fibre (8.1 to 10.3%) contents. Although consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Currently, goat meat does not have a wide range of consumers in the Republic of Kazakhstan. However, active scientific research on using this type of raw meat in the industry is already underway in the world and has great prospects in the domestic market [2], [3], [4], [5], [6], [7], [8]. Regarding taste, goat meat is not inferior to mutton [9].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, goat meat does not have a wide range of consumers in the Republic of Kazakhstan. However, active scientific research on using this type of raw meat in the industry is already underway in the world and has great prospects in the domestic market [2], [3], [4], [5], [6], [7], [8]. Regarding taste, goat meat is not inferior to mutton [9].…”
Section: Introductionmentioning
confidence: 99%
“…It can be a functional and nutritious supplement (Devi et al, 2021). It is also used as one of the carbohydrate fillers in some healthy foods, where it is an inexpensive filler (Sujarwanta et al, 2021). Sorgeloos et al (1980) and Vanhaecke and Sorgeloos (1989) studied the effect of rice bran in comparison to microalgae Dunaliella on the length of Artemia within seven days; the results showed that the rice bran gave higher results.…”
mentioning
confidence: 99%